The effect of nintedanib versus mycophenolate mofetil in the Fra2 mouse model of systemic sclerosis-associated interstitial lung disease. - Wollin, Lutz; Trinh, Minh Thuong; Zhang, Yun; Distler, Jörg (Clinical and Experimental Rheumatology, 2021)
OBJECTIVES: Interstitial lung disease (ILD) is a key driver of mortality in patients with systemic sclerosis (SSc). A lack of approved treatments encompasses a high unmet medical need. Nintedanib has recently been approved for treatment in SSc-associated ILD (SSc-ILD) following SENSCIS®, a Phase III clinical trial showing that nintedanib slows the loss of pulmonary function in patients with SSc-ILD relative to placebo, as measured by annual rate of decline in forced vital capacity over 52 weeks. The aim of this study was to compare the activity of nintedanib and mycophenolate mofetil (MMF) in a transgenic Fra2 mouse model of SSc-ILD. METHODS: Fra2 transgenic mice were treated with MMF or nintedanib. Haematoxylin and Eosin and Sirius Red staining were used to identify pulmonary fibrosis and vascular remodelling in whole lung sections. Fibrosis was quantified by Ashcroft scoring, fold change in fibrotic area, and hydroxyproline. Ki67, SM22a, CD31, and caspase-3 staining was used to quantify proliferating vascular smooth muscle cells and apoptotic endothelial cells. RESULTS: Nintedanib effectively ameliorated pulmonary vascular remodelling and fibrosis in Fra2 transgenic mice. Pulmonary fibrotic and vascular remodelling parameter scores and the apoptosis of dermal endothelial cells were significantly reduced compared with vehicle-treated Fra2 transgenic mice. Treatment with MMF had only mild antifibrotic effects and no effect on pulmonary vascular remodelling. CONCLUSIONS: In this model of SSc-ILD, nintedanib ameliorated pulmonary fibrosis, remodelling of pulmonary vasculature, and the apoptosis of endothelial cells. In contrast, MMF had minor effects on pulmonary fibrosis and no effects on vascular manifestations.
EVALuna2:486833
Keywords: systemic sclerosis; interstitial lung disease; nintedanib; mycophenolate mofetil; fibrosis